IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PEMBELAJARAN PPKN DI SEKOLAH DASAR - Devada Yesyana Anggita Putri; Yuan Sifa Sasikirana; Dea Lovita Indratama; Nhabila Belinda Innova; Syalwa Hidayati; Callista Rahma Elya Fatika Sari (Universitas PGRI Madiun, 2026)
This study aims to examine the implementation of Pancasila values in Civics (PPKn) learning at elementary schools to build students' character amid the moral degradation challenges posed by digitalization. A qualitative approach with a literature study method was employed, analyzing scientific articles, textbooks, and ministerial regulations from the last ten years through Miles and Huberman's thematic analysis and source triangulation. The results show that the five principles of Pancasila are structurally integrated through joint worship habituation, peer tutoring, mutual cooperation, deliberation, and equal learning rights, with the highest mean score found in the aspect of togetherness and consensus deliberation (82.15). However, external factors such as unfiltered gadget exposure and weak parental supervision dominate implementation barriers, reaching 65%. Multiple linear regression analysis confirms the significant contribution of value-based pedagogical innovation (R² = 0.709) to strengthening students' character. This study recommends strengthening the tricenter education synergy among schools, families, and communities, as well as transforming conventional teaching methods into interactive digital-based models.